Regulation of mRNA Translation Is a Novel Mechanism for Phthalate Toxicity - Ling, Jun; Lopez-Dee, Zenaida P.; Cottell, Colby; Wolfe, Laura; Nye, Derek (PLOS ONE, 2016)
Phthalates are a group of plasticizers that are widely used in many consumer products and medical devices, thus generating a huge burden to human health. Phthalates have been known to cause a number of developmental and reproductive disorders functioning as endocrine modulators. They are also involved in carcinogenesis with mechanisms less understood. To further understand the molecular mechanisms of phthalate toxicity, in this study we reported a new effect of phthalates on mRNA translation/protein synthesis, a key regulatory step of gene expression. Butyl benzyl phthalate (BBP) was found to directly inhibit mRNA translation in vitro but showed a complicated pattern of affecting mRNA translation in cells. In human kidney embryonic cell (HEK-293T), BBP increased cap-dependent mRNA translation at lower concentrations but showed inhibitory effect at higher concentrations. Cap-independent translation was not affected. On the other hand, mono (2-ethylhexyl) phthalate (MEHP) as a major metabolite of another important phthalate di (2-ethylhexyl) phthalate (DEHP) inhibited both can-dependent and -independent mRNA translation in vivo. In contrast, BBP and MEHP exhibited an overall promoting effect on mRNA translation in cancer cells. Mechanistic studies identified that the level and phosphorylation of eIF4E-BP (eIF4E binding protein) and the amount of eIF4GI in eIF4F complex were altered in accordance with the effect of BBP on translation. BBP was also identified to directly bind to eIF4E, providing a further mechanism underlying the regulation of mRNA by phthalate. At the cellular level BBP inhibited normal cell growth but slightly promoted cancer cells (HT29) growth. Overall, this study provides the first evidence that phthalates can directly regulate mRNA translation as a novel mechanism to mediate their biological toxicities.